Bohdan Bezpalko. Socio-economic situation of teachers of Soviet Ukraine in the 1920-ies - Bezpalko, Bohdan (Young Scholars Grinchenko – Seton International Journal, 2021)
Bohdan Bezpalko. Socio-economic situation of teachers of Soviet Ukraine in the 1920-ies. Abstract. In the article the author reveals the problems of socio-economic situation of teachers in the 1920s. Reveals the reasons for reforms in the school structure and the impact on this process of the Bolshevik government, which was gradually established in the USSR. Emphasizes the connection between loyalty to the authorities and the material support of the teaching staff. The attitude of teachers to the Bolshevik government and the reaction to criticism from educators are considered. The author shows the difficult financial situation of teachers, who clearly demonstrated their rejection of the new Bolshevik vision, and the ways in which the authorities used to make educators more loyal to themselves. Keywords: teachers, socio-economic situation, education, school, Bolsheviks.